2020
DOI: 10.3390/ncrna6020020
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Technologies to Study RNA–Chromatin Interactions

Abstract: An increasing number of studies have revealed that long non-coding RNAs (lncRNAs) play important roles in gene regulation and nuclear organization. Although the mechanisms are still largely unknown, many lncRNAs have been shown to interact with chromatin. Thus, one approach to understanding the function of these lncRNAs is to identify their sites of genomic interaction. Hybridization capture methods using oligonucleotide probes have been used for years to study chromatin-associated RNA. Recently, several group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Recent genome-wide proteomic studies have identified many new RBPs [ 2 , 210 ]. Those newly identified RBPs are conserved from yeast to humans.…”
Section: Chromatin Associated Non-coding Rnas and Acting Modes In Chromatin Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent genome-wide proteomic studies have identified many new RBPs [ 2 , 210 ]. Those newly identified RBPs are conserved from yeast to humans.…”
Section: Chromatin Associated Non-coding Rnas and Acting Modes In Chromatin Remodelingmentioning
confidence: 99%
“…Those newly identified RBPs are conserved from yeast to humans. Despite lacking the conventional or canonical RBDs, those new RBPs can modulate chromatin structure and gene expression in response to various environmental and intrinsic stimuli [ 2 , 210 , 211 , 212 , 213 ]. Both canonical and non-canonical RBPs are reported to function together to regulate transcription and chromatin structure [ 214 , 215 ].…”
Section: Chromatin Associated Non-coding Rnas and Acting Modes In Chromatin Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a deep learning model can help identify such generic features in an ab-initio manner. When trained on existing known lncRNAs examples it can pick up similar patterns on screening the transcripts obtained in RNA-seq experiments en masse [30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data implies that at least 80% of the human genome is transcribed, producing about 20,000 messenger RNAs (mRNAs), over 2300 microRNAs (miRNAs), a set of structural RNAs (such as ribosomal RNAs (rRNAs), transfer RNAs (tRNAs), and small nuclear RNAs (snRNAs)), and at least 50,000 long noncoding RNAs (lncRNAs) [ 1 , 2 , 3 ]. LncRNAs comprise a diverse group of non-protein coding transcripts that are longer than 200 nucleotides in length, lack an open reading frame, and regulate gene expression at many levels by affecting transcription, cellular localization, mRNA stability, translation, and other post-transcriptional events [ 4 , 5 , 6 , 7 ]. As a result, lncRNAs regulate a broad range of biological processes, including aging, cell growth and differentiation, hematopoiesis, and immune response [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%